IMPLEMENTATION OF PEER LESSONS LEARNING STRATEGY TO IMPROVE STUDENTS LEARNING OUTCOMES SCIENCE ON CLASS V SD - Nurfauziah Nurfauziah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This research is motivated by the still weak learning outcomes of science students in grade V of SD Negeri 021 Tarai Bangun. The purpose of this study is to improve student science learning outcomes by implementing peer lessons learning strategies. This type of research uses classroom action research consisting of two cycles. Each cycle consists of 4 stages such as: 1) planning; 2) implementation; 3) observations / observations; and 4) reflection. The results of this study showed the average percentage of student learning outcomes before the action only reached an average of 54.3%. In the first cycle student learning outcomes increased to 66.6% or with a classification of moderate values, and in the second cycle again increased to 80.5% with a classification of good grades. Based on these results it can be concluded that by implementing the peer lessons learning strategy can improve the science learning outcomes of fifth-grade students of SD Negeri 021 Tarai Bangun.